A Contrastive Study of Reflexive verbs in English and French - KANE, Hafissatou (Journal of English Language Teaching and Applied Linguistics, 2021)
This paper describes and compares reflexive verbs in English and French. In collecting the data, a number of books and research works related to the subject have been analysed, using the contrastive method. Results of the analysis indicate that reflexives display a great difference between the two languages. The main observed similarity occurs with the emphatic form. Indeed, the English pronouns “myself”, “himself”, “ourselves” etc, and their French counterparts moi-même, lui-même, nous-mêmes are used in the same way. Points of differences are presented as follows: while French puts the pronominal clitics me, te, se, nous, vous before the verb, English places pronouns after e.g., se blesser “to hurt oneself”. One of most important differences that several verbs take reflexive pronouns in French while their English counterparts don’t e.g., se demander “to wonder”. It has also been noted that, in English, the same pronouns are used to express both emphatic and non-emphatic forms while French distinctively uses toi-même, elles- mêmes etc. to emphasize; and the pronominal clitics in simple forms. In the reciprocal voice, the English pronouns “each other” and “one another” are less ambiguous than their French corresponding ones. For instance, Nous nous aimons means both “we love ourselves” (reflexivity) and “we love each other / one another” (reciprocity). Finally, it is shown that some English verbs do not appear with reciprocal pronouns but their French equivalents do e.g., “to meet” se rencontrer.